2015
DOI: 10.1002/2014jf003224
|View full text |Cite
|
Sign up to set email alerts
|

Regional coseismic landslide hazard assessment without historical landslide inventories: A new approach

Abstract: Currently, regional coseismic landslide hazard analyses require comprehensive historical landslide inventories as well as detailed geotechnical data. Consequently, such analyses have not been possible where these data are not available. A new approach is proposed herein to assess coseismic landslide hazard at regional scale for specific earthquake scenarios in areas without historical landslide inventories. The proposed model employs fuzzy logic and geographic information systems to establish relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 101 publications
(156 reference statements)
1
100
1
Order By: Relevance
“…By general rules of thumb, AUC values greater than 0.8 represent good classification performance (e.g. : Mehdi, 2011), while to be successful predictions must achieve an AUC value of 0.7 (Kritikos et al, 2015). AUC values for individual events range from 0.75 to 0.88 ( Figure 5).…”
Section: Model Fitmentioning
confidence: 95%
See 2 more Smart Citations
“…By general rules of thumb, AUC values greater than 0.8 represent good classification performance (e.g. : Mehdi, 2011), while to be successful predictions must achieve an AUC value of 0.7 (Kritikos et al, 2015). AUC values for individual events range from 0.75 to 0.88 ( Figure 5).…”
Section: Model Fitmentioning
confidence: 95%
“…Methods using data from multiple earthquakes, to derive statistical models generalized at 1 km 2 resolution (Nowicki et al, 2014), and 90 m resolution (Kritikos et al, 2015), have had some success. These models perform well in identifying the likely locations of landslides in the landscape, based upon a relatively small number of earthquakes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies to date have addressed spatial correlations between the distribution of landslides and variables that provide proxies for seismic ground motions and the modelled stability of hillslopes (e.g. Dai et al, 2011;Meunier et al, 2007Meunier et al, , 2008; Kritikos et al, 2015). These studies implicitly rely upon a static model of hillslope sensitivity to landslide triggering.…”
Section: Introductionmentioning
confidence: 99%
“…A rapid appraisal of the first available imagery suggested that landsliding occurred in an E-W swath located north of the Kathmandu Valley, covering a large proportion of western and central Nepal (∼ 12 000 km 2 ). Initial indications from coseismic earthquake-triggered landslide models, based on Kritikos et al (2015) and Parker et al (2017), were used to direct the mapping effort (see http://ewf.nerc.ac.uk/2015/ 04/25/nepal-earthquake-likely-areas-of-landsliding/). However, mapping efforts were constrained by widespread cloud cover that limited the availability of good-quality optical imagery.…”
Section: Initial Landslide Identification Effortsmentioning
confidence: 99%